Utilization of Zakat Infaq and Alms for ASN Binjai Government through Baznas to Improve Community Welfare in Binjai City - Arnadila Dwi Syahputri; Andri Soemitra (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
One of the efforts to reduce the poverty rate in Binjai City is by utilizing Zakat, Infaq and Sadaqah (ZIS). Zakat, Infaq and Sadaqah (ZIS) of the Binjai Government Civil Apparatus (ASN) with a total of 2.5% is obtained from the salary of each employee at the Binjai Government which is then distributed through Baznas. This study looks at the utilization of Zakat, Infaq and Sadaqah (ZIS) for the Binjai Government Civil Service Apparatus (ASN), in order to improve community welfare and reduce poverty levels. The management of zakat which starts from collecting, distributing and then making accountability reports is all based on Law Number 23 of 2011 concerning zakat management. The results showed that the distribution of Zakat, Infaq and Sadaqah (ZIS) for the State Civil Apparatus (ASN) of the Binjai Government through Baznas was intended for 8 categories of people who were entitled to receive zakat according to Islamic teachings. The distribution and utilization of Zakat, Infaq and Sadaqah (ZIS) for the Binjai Government Civil Service Apparatus (ASN) generally consists of assistance in the fields of health, education and social empowerment. The accountability report was handed back to the Pemko Binjai with transparency in the reporting system that was quite good.